Choice of a way to verify space-occupying lesions of the breast at a preoperative stage - N. V. Ponedelnikova; G. P. Korzhenkova; V. P. Letyagin; Ya. V. Vishnevskaya (Опухоли женской репродуктивной системы)
Preoperative verification of breast cancer (BC) is a necessary stage of diagnosis. The main method for obtaining materials is fine-needle aspiration biopsy that is of low informative value in a number of cases. Histological biopsy of nonpalpable breast masses extends the verification capabilities of accurate diagnosis and determines the choice and tactics of combination and complex treatments in patients with BC just at a preoperative stage, and, in case of detection of a benign tumor, enables one to abandon sector resection with an urgent histological study.